Interactions of pathogenic Escherichia coli with CEACAMs - Sheikh, Alaullah; Fleckenstein, James M. (Frontiers in Immunology, 2023)
The pathogenic Escherichia coli can be parsed into specific variants (pathovars) depending on their phenotypic behavior and/or expression of specific virulence factors. These pathogens are built around chromosomally encoded core attributes through acquisition of specific virulence genes that direct their interaction with the host. Engagement of E. coli pathovars with CEACAMs is determined both by core elements common to all E. coli as well as extrachromosomally-encoded pathovar-specific virulence traits, which target highly conserved amino terminal immunoglobulin variable-like (IgV) regions of CEACAMs. Emerging data suggests that engagement of CEACAMs does not unilaterally benefit the pathogen and that these interactions may also provide an avenue for pathogen elimination.